Dream recording frequency in psychology students - Schredl, Michael (International journal of dream research, 2020)
Previous research has indicated that dream recording frequency is associated with openness to experience and also low conscientiousness. Although psychology students are likely to be interested in topics like dreaming, systematic studies about their dream recording behavior have not been carried out. In this analysis, the dream recording frequencies of 409 psychology students was compared to the dream recording frequencies of a population-based sample (N = 1742) using the same 8-point rating scale. The findings indicated that psychology students record their dreams more often than the population-based survey participants - differences in dream recall frequency were statistically controlled. From a methodological viewpoint, dream researchers have to be careful when generalizing their findings based on samples of dream journalists who show specific trait characteristics that are different compared to the general population. From a theoretical viewpoint, it would be interesting to learn more about the motives as to why individuals keep dream journals.
Gesehen am 19.10.2020